Leveraging crowdsourcing to facilitate the discovery of new medicines. - Norman, T; Bountra, C; Edwards, A; Yamamoto, K; Friend, S (2011)
Gloomy predictions about the future of pharma have forced the industry to investigate alternative models of drug discovery. Public-private partnerships (PPPs) have the potential to revitalize the discovery and development of first-in-class therapeutics. The new PPP Arch2POCM hopes to foster biomedical innovation through precompetitive validation of pioneer therapeutic targets for human diseases. In this meeting report, we capture insights garnered from the April 2011 Arch2POCM conference.